2014
DOI: 10.1007/s00422-014-0594-6
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in robot psychology

Abstract: In his famous thought experiments on synthetic vehicles, Valentino Braitenberg stipulated that simple stimulus-response reactions in an organism could evoke the appearance of complex behavior, which, to the unsuspecting human observer, may even appear to be driven by emotions such as fear, aggression, and even love (Braitenberg, Vehikel. Experimente mit künstlichen Wesen, Lit Verlag, 2004). In fact, humans appear to have a strong propensity to anthropomorphize, driven by our inherent desire for predictability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Emotion expressed through the face is also considered to be especially important as a means for communicating evaluations and appraisals (Parkinson, 1996). Given the importance of facial expressions to the communication of human affect, they should also have significant potential as a communication means for humanoid robots (Nitsch, & Popp, 2014). This intuition has led to the development of many robot platforms with the capacity to produce human-like facial expression, ranging from the more iconic/cartoon-like (e.g., Breazeal, 2003;Ros, et al 2011) to the more natural/realistic (e.g., -Asano, & Ishiguro, 2011;Mazzei, Lazzeri, Hanson, & De Rossi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Emotion expressed through the face is also considered to be especially important as a means for communicating evaluations and appraisals (Parkinson, 1996). Given the importance of facial expressions to the communication of human affect, they should also have significant potential as a communication means for humanoid robots (Nitsch, & Popp, 2014). This intuition has led to the development of many robot platforms with the capacity to produce human-like facial expression, ranging from the more iconic/cartoon-like (e.g., Breazeal, 2003;Ros, et al 2011) to the more natural/realistic (e.g., -Asano, & Ishiguro, 2011;Mazzei, Lazzeri, Hanson, & De Rossi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years impressive improvements have been achieved in this field and it has been proved by separate studies that humans can successfully recognize emotions displayed by a humanoid face of robots or virtual agents (see also the above mentioned studies and for other examples e.g. [19] , [20] ; or for a review see [21] ). Moreover, some studies provided evidence suggesting that emotions expressed by a humanoid robot face evoke similar emotions in humans as well (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some studies provided evidence suggesting that emotions expressed by a humanoid robot face evoke similar emotions in humans as well (e.g. [22] , for a review see [21] ). Although, a recent study of Chaminade et al [23] showed that on the level of neural responses humans react differently to the emotional expressions of a humanoid robot and of a human.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Every step in technology, added new aspects to the development of machines; machines which have the strength and abilities to do things like a human! Their potential abilities are growing with the research in psychology, neuroscience, and computer science and engineering (Nitsch & Popp, 2014). And finally, with these steps we started to see the reality of artificial intelligence.…”
Section: Introductionmentioning
confidence: 99%